Chinese Religions Going Global - Cao, Nanlai (Annual Review of the Sociology of Religion Ser., 2020)
Half Title -- Series Information -- Title Page -- Copyright Page -- Contents -- Preface -- Acknowledgements -- Notes on Contributors -- Chapter 1 Bargaining with God in the Name of Family: Chinese Christian Entrepreneurs in Italian Coffee Bars -- 1 As Immigrant Entrepreneurs -- 2 As Christians -- 3 Moral Dilemmas in the Neighborhood Bar Business -- 4 Negotiating Religious Morality -- 4.1 Clientele Management -- 4.2 Time Management -- 5 Family Values as Bridging Ethics -- 6 Conclusion -- Acknowledgements -- References -- Chapter 2 From China with Faith: Sinicizing Christianity in Europe -- 1 The Rise of a Household-Based Chinese Christianity in Diaspora -- 2 Migrant Entrepreneurship and Lay Leadership -- 3 Repaying China's "Gospel Debts" to Europe -- 4 Conclusion -- References -- Chapter 3 A Bridge between the Spiritual and the Worldly: The Puhuasi Buddhist Temple in Prato (Italy) -- 1 Introduction -- 2 Chinese Population in Prato -- 3 Chinese Flexible Religiosity and the Forms It Has Taken in Prato -- 4 The "Social" Function of the Puhuasi -- 5 Who Attends the Puhuasi and Why -- 6 Between Faith, Cultural Identity and Material Needs -- 7 Some Conclusions -- References -- Chapter 4 Exploring Chinese Catholicism in the Italian Peninsula: A Sociological Study of the Chinese Catholic Community in Italy -- 1 Introduction -- 2 The Spread of Chinese Catholic Communities in the Italian Peninsula -- 3 A Sociological Overview of the Chinese Catholic Community in Italy -- 4 Patterns of Settlement of Chinese Catholic Communities in Italy -- 5 Examining Religious Transnationalism within Chinese Catholicism in Italy -- 6 Conclusions -- References -- Chapter 5 Encounter, Initiation, and Commitment: Christian Conversion among New Chinese Migrants in Britain -- 1 Introduction: The Chinese Christians in Britain -- 2 Religious Conversion: A Processual Model.